2010
DOI: 10.1590/s0100-29452010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticabeiras

Abstract: The jabuticaba tree (Plinia sp.) belongs to the Myrtaceae family and is native from the Central, the South and the Southeast Brazil, with a secondary center of spreading in Paraguay and Argentina. Nine species are known, one is considered extinct, five are only found in some research sites, and only three have natural dispersion and in crops in Brazil. These last ones are: Plinia trunciflora (Berg) Mattos (jabuticaba of stalk); Plinia cauliflora (DC.) Berg (jabuticaba Paulista ponhema or assu) and Plinia jabot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
10
0
4
Order By: Relevance
“…Jabuticabeira is a fruit tree belonging to the Myrtaceae family, which occurs spontaneously in large part of Brazil. It originates from the south region of the country; however, it can be found from the state of Pará until the state of Rio Grande do Sul (Brunini and others ; Citadin and others ). Most jabuticaba species cultivated in Brazil are Sabará jabuticaba ( Myrciaria jabuticaba ), which is the most appreciated because the fruit is small and sweet, and Paulista jabuticaba ( Myrciaria cauliflora ), which has a thick skin and because it has a lower sweet taste (Costa and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Jabuticabeira is a fruit tree belonging to the Myrtaceae family, which occurs spontaneously in large part of Brazil. It originates from the south region of the country; however, it can be found from the state of Pará until the state of Rio Grande do Sul (Brunini and others ; Citadin and others ). Most jabuticaba species cultivated in Brazil are Sabará jabuticaba ( Myrciaria jabuticaba ), which is the most appreciated because the fruit is small and sweet, and Paulista jabuticaba ( Myrciaria cauliflora ), which has a thick skin and because it has a lower sweet taste (Costa and others ).…”
Section: Introductionmentioning
confidence: 99%
“…9, 2010 and in other parts of South America. 5 Citadin et al 6 have reported that natural shade or full sunlight tree development have not shown differences as regards physico-chemical features of fruit quality. The jaboticaba bagasse flour, which is a good source of fiber, proteins and minerals is made up of fine particles which have the fruit's aroma and its taste is slight salty and bitter.…”
Section: Introductionmentioning
confidence: 99%
“…The jabuticaba commercialization has been going through difficulties because this fruit is highly perishable presenting a short period of consumption due to its high content of water and sugars [6]. Thinking of improvements for the preservation of this fruit, the drying process has been used to remove the water of the product through the heat having the heat and mass transfer with water removal and consequent reduction of microbial growth and enzymatic reactions [7].…”
Section: Introductionmentioning
confidence: 99%